Social Change and Criminality in Istanbul - Nilgun Ergun; Cengiz Giritlioglu; Funda Yirmibesoglu (European Regional Science Association (ERSA), 2003)
Many researchers and urban planners have made studies about security in city centers. One of the prerequisites for the continuous development of cities is to establish a safe environment. The deficiencies observed in the social equipment, infrastructure and the environmental conditions as well as social, economic, cultural and political structural characteristics of the society are factors that increase or decrease crime and criminality. The purpose of this paper is to investigate the differentiation, which has appeared during the stage of economic development, and the socio-cultural differentiation in the Istanbul metropolitan historical center. The study examines how physical characteristics of city centers and demographic characteristics of residential areas contribute to crime and how these characteristics affect reactions to crime in mixed commercial/residential areas. The data are collected to examine the relationship between crime rates and neighborhood structure in Istanbul old city center between 1993-1998. Information on physical characteristics includes type of land uses and demographic variables include age, education, average household size and income, percent change of occupancy. Key words: Crime, city center, social change, physical and demographical variable
Keywords: 330